Ellie engineer : the next level - Pearce, Jackson (New York : Bloomsbury, 2018)
When Ellie and her friends help elderly Mrs. Curran around the house, Ellie cannot resist using her engineering prowess but it is no fun for the girls when Toby gets the credit.
Keywords: Engineering -- Fiction; Building -- Fiction; Sex role -- Fiction; Friendship -- Fiction; Neighborliness -- Fiction